2021
DOI: 10.3389/fneur.2021.704329
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience With the Trevo NXT Stent Retriever

Abstract: Background: The application of a new coating to the delivery wire of the Trevo retriever has the potential to improve its handling. We therefore report our initial experience with this new stent retriever for mechanical thrombectomy of large and medium vessel occlusions.Methods: We pooled data of four high-volume European stroke centers over the time period from October 2020 to February 2021. Patients were included in our study if the Trevo NXT stent retriever was used as a first-line device. Primary endpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The authors reported only two cases of vasospasm and no cases of symptomatic intracranial hemorrhage. Despite being originally developed for use in PLVO, this mini stent retriever showed similar or better rates of recanalization in this study when used in M2 occlusions (22/22, 100%) compared with cases of PLVO (M1 or ICA-terminus, 49/52, 94%) and, interestingly, required less passes on average (1.0 passes for DMSVO and 1.5 passes for PLVO) [ 59 ]. Although further multicenter, randomized studies are warranted to further support the efficacy of using mini stent retrievers for DMSVOs, this new generation of mini-stent retrievers appears, in early studies, to be safe and feasible for a variety of vessel sizes due to its adaptable, low-profile design and maneuverability.…”
Section: Intervention Techniquesmentioning
confidence: 73%
See 1 more Smart Citation
“…The authors reported only two cases of vasospasm and no cases of symptomatic intracranial hemorrhage. Despite being originally developed for use in PLVO, this mini stent retriever showed similar or better rates of recanalization in this study when used in M2 occlusions (22/22, 100%) compared with cases of PLVO (M1 or ICA-terminus, 49/52, 94%) and, interestingly, required less passes on average (1.0 passes for DMSVO and 1.5 passes for PLVO) [ 59 ]. Although further multicenter, randomized studies are warranted to further support the efficacy of using mini stent retrievers for DMSVOs, this new generation of mini-stent retrievers appears, in early studies, to be safe and feasible for a variety of vessel sizes due to its adaptable, low-profile design and maneuverability.…”
Section: Intervention Techniquesmentioning
confidence: 73%
“…Interestingly, this study used the Tigertriever 13 stent in a wide variety of both anterior and posterior circulation DMSVOs, demonstrating the adaptability as well as the safety and feasibility of using this low-profile stent retriever in the treatment of DMSVO [ 13 ]. Etter et al used the 3 and 4 mm Trevo NXT Provue Retriever (Stryker, Freemont, CA, USA) in 22 patients with M2 occlusion and achieved a 100% final reperfusion rate mTICI ≥ 2b (86% mTICI ≥ 2c, 59% mTICI 3), with an average pass number of 1 [ 59 ]. The authors reported only two cases of vasospasm and no cases of symptomatic intracranial hemorrhage.…”
Section: Intervention Techniquesmentioning
confidence: 99%
“…Mechanical retrieval, on the other hand, utilizes catheter-based devices to remove the thrombus. Stent retriever devices, such as the Trevo TM and Solitaire TM , are used to “grab” the clot by mechanical interference, allowing the clot to be pulled out along with the catheter [ 15 , 16 ]. Aspiration guide catheters, such as the Penumbra, provide suction to assist in removal [ 2 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The subjective experience of interventionalists with the MT device was surveyed using an ordinal 5-point scale, with 1–5 reflecting very easy, easy, neutral, hard and very hard, respectively. 11 …”
Section: Methodsmentioning
confidence: 99%